Two new species of Metrichia Ross 1938 (Trichoptera: Hydroptilidae) from the Brazilian Amazon biome - Neto, Jaime De Liege Gama; Passos, Mahedy Araujo Bastos (Zootaxa, 2024)
Two new species of Metrichia from Roraima State, Brazil, are described and illustrated, representing additional records of Metrichia from the Brazilian Amazon biome. The male of Metrichia iracema sp nov. is characterized by inferior appendages each elongate, with an acute apical projection and a deep C-shaped notch, tergum X apex slightly incised, and dorsal hook with a longer dorsal branch extending anterad. Metrichia camposnovos sp nov. is characterized by inferior appendages each subtrapezoidal and with acute apical corners, and phallus tubular, elongate, and slender, with a median process and with two curved subapical spines arising at the same level, one curved to the left, another curved to the right.